Reviewing Optimized Portfolios: All Seasons Strategy - D. Navas, Raúl; R. Bentes, Sónia (Review of Business Management, 2022)
Purpose – Our research revisits the study “Optimized Portfolios: All Seasons Strategy,” where we support diversified portfolios to minimize risk, considering the principle of Markowitz. Theoretical framework – We re-examine the results of Navas et al. (2020). The idea behind this is the theory of Harry Markowitz (1959, 2010), regarded as the founder of modern portfolio theory. Design/methodology/approach – Six different models are run using data from 2000 to 2010 and a solver is developed, where the GRG Nonlinear engine for linear solver problems is the solving process chosen. Findings – The GRG Nonlinear engine is efficient if we take into account ways to lower volatility since it is inversely correlated to predictions. Practical & social implications of research – To predict the composition of the portfolios, we do not take into consideration the crash of gold and precious metals in 2013. Originality/value – Robust portfolios can be generated where the risk is minimized and the return is maximized. Keywords – MPT, Markowitz, portfolio formation, Sharpe ratio, volatility